The Effect of Problem Based Learning to Improve Students' Creative Thinking Abilities - Syaiful Wibowo; Eko Suyanto; I Dewa Putu Nyeneng (Jurnal Pembelajaran Fisika, 2021)
This study was aimed to determine students' creative thinking abilities after being given a problem-based learning (PBL) model with practicum method on energy conversion material. The Quasi-experiment with one group pretest-posttest design was used in this study. The measurement of the effect of students' creative thinking abilities uses 10 questions of creative thinking abilities with indicators, i.e. elaboration and flexibility. The questions were given to students before and after being treated and the results of the data were analyzed using paired sample T-Test and N-Gain. Hypothesis test results about the effect of students' creative thinking abilities using problem-based learning models with practicum on energy conversion material obtained asymp sig values. (2 tailed) of 0.001 and the value of N-Gain is 0,672. Based on these results, it is known that students experience an increase in the ability to think creatively after being given learning with a problem-based learning model with practicum methods on energy conversion material. Therefore, problem-based learning models with the practicum method affects students' creative thinking abilities on energy conversion material. Keywords: Creative thinking, Practicum method, PBLDOI: http://dx.doi.org/10.23960/jpf.v9.n1.202102